An analysis of fieldwork implementation in the teaching and learning of physical Geography at Ordinary Level. - Dube, Sipiwe (Midlands State University, 2020)
Fieldwork is regarded as any curriculum component that involves leaving the classroom to engage in teaching and learning activities through first-hand experience of outdoors phenomena. Most Geographers regard fieldwork as being central to research, teaching and intrinsic to their nature. The study sought to establish how fieldwork was being implemented in schools, its value in Geography teaching and learning, the challenges associated with its implementation and how it could be enhanced as well. A descriptive survey design was employed and interviews and questionnaires were used to collect data from respondents. Two secondary schools in Gweru District made up the population whereby twenty pupils, eight teachers and two heads of department constituted the sample. The simple random, snowball and purposive sampling techniques were used in selecting pupils, teachers and heads of department respectively. Data was presented in form of tables, bar graphs, line graphs and pie charts and analysed through the use of codes, themes and patterns. It was revealed by the study that fieldwork enhanced the learning of concepts, skills and topics in physical Geography. It also gave reality to Geography and saved the subject from being rigid and theoretical. Despite its value, fieldwork was being conducted less frequent in schools due to various challenges which include, lack of adequate research resources, limited time due to the need to complete the syllabi, large classes, financial constraints, geographical landscape and poor administrative and parental support. The study therefore recommended the Ministry of Primary and Secondary Education to deploy more Geography teachers in schools. It also recommended the schools to conduct more workshops based on fieldwork implementation whereby the school administrators are also taught and encouraged to appreciate the value of fieldwork.